Hubungan Bentuk-bentuk Perilaku Orangtua dengan Perkembangan Emosi Remaja pada Siswa : Studi Kasus SMK Negeri 2 Tanjung Pinang - Harmida Hutajulu (Cendikia : Media Jurnal Ilmiah Pendidikan, 2020)
This research was conducted at SMK Negeri 2 Tanjung Pinang. Sampling is done by random sampling. The sample number was 34. Data collection is done using questionnaires of forms of people's behavior and adolescent emotional development. Data analysis is done by means of descriptive analysis techniques and product moment correlation techniques. From the results of the study obtained: Forms of parental behavior of students distributed in high categories(26.47%), high distribution (44.12%), sufficient distribution (17.65%) and distribution less (11.76%). Students' emotional development falls into the highly high category (23.53%), high-distribution (47.06%), sufficiently distributed (17.65%) and less distributed (11.76%). These forms of student parental behavior, significantly correlated with adolescent (student) emotional development at a 5% confidence level (rxy = -0.43). Large contributions made by forms of parental behavior to the emotional development of adolescents (students) by 18.5% (r2 = 0.185).